Comparison between transrectal palpation, B-mode and Doppler ultrasonography to assess luteal function in Holstein cattle - Yáñez, Uxía; Murillo, Antonio V.; Becerra, Juan J.; Herradón, Pedro G.; Peña, Ana I.; Quintela, Luis A. (Frontiers in Veterinary Science, 2023)
Over the years, the most common methods for monitoring reproductive health in cattle have varied from transrectal palpation to B-mode ultrasonography. Nowadays, some portable ultrasound equipment includes the Doppler mode. Therefore, the aim of this study was to compare the accuracy of the different methods to assess corpus luteum (CL) functionality. In experiment 1, 53 Holstein lactating cows undergoing a synchronization protocol were examined via transrectal palpation and B-mode scanning. Measurements for the largest diameter (LAD) and subjective size of CL (SCLS) were collected. Data were analyzed using correlation analysis and ROC Curves. In experiment 2, 30 Holstein non-lactating cows with a CL were administered PGF2α and examined several times after injection, first in B-mode and then with Power Doppler. Measurements for LAD, CL area (CLA) and subjective and objective CL blood flow were collected. Data were analyzed using correlation analysis and the GLM repeated measures test. Blood samples were taken in both experiments to determine P4 concentration. Results for experiment 1 showed that LAD was more accurate than SCLS. In experiment 2, CLA was the best measurement to assess CL function, although both subjective and objective CL blood flow offer accurate information 24h after PGF2α administration. Consequently, ultrasonography provides more accurate information about CL function than transrectal palpation. Although CLA seems to be an earlier indicator of luteal function than blood flow, 24h after the onset of luteolysis, both parameters are valid.